No racism, no ethnic monitoring - CPSA leaflet, 1982 (London, 1982)
1982 1980-95 "No racism, no ethnic monitoring - CPSA leaflet, 1982" [BW0193], 1982, Trades Union Congress Leaflet from the Civil and Public Services Association opposing the policy of recording claimants' ethnic group in Unemployment Benefit Offices.